Vagrants and vagabonds: poverty and mobility in the early American republic - O'Brassill-Kulfan, Kristin (Early American places, 2019)
"Vagrants and Vagabonds: Poverty and Mobility in the Early American Republic" explores the topics of social class and poverty and their implications in the early American republic.--Provided by publisher